IMPLEMENTASI PENDEKATAN TEKNOLOGI DALAM PENGEMBANGAN KURIKULUM MERDEKA PADA PEMBELAJARAN BAHASA ARAB DI MTS MATSARATUL HUDA PANEMPAN PAMEKASAN - Wardatul Humairoh, Sitti; Ubaidillah, Moch. (LPPM STAI Muhammadiyah Probolinggo, 2025)
Curriculum development with a technological approach is a relevant model to be implemented at MTs Matsartul Huda Panempan Pamekasan, especially in the current era of the industrial revolution. This approach is felt to be very appropriate to the needs of the times, so it is important to be integrated into curriculum development at the elementary school level. Moreover, the independent curriculum currently being implemented aims to provide students with greater flexibility in directing their learning process. This research aims to explore and analyze the use of a technological approach in developing an independent curriculum for Arabic language learning at MTs Matsaratul Huda Panempan Pamekasan. This research uses descriptive qualitative research methods. Determine data collection techniques using interviews, observation and documentation. The use of technology to develop a free curriculum for learning Arabic at MTs Matsaratul Huda Panempan Pamekasan has become relevant and effective, in line with the characteristics of the current generation. The use of technology can improve the quality of learning, help students to improve skills relevant to the digital era and prepare them to face change and innovation. In this way, the use of technology in the Arabic language learning process becomes more measurable, creative and relevant to the needs of the current generation.